DAMPAK DESENTRALISASI FISKAL TERHADAP OUTPUT, PENDAPATAN, KESEMPATAN KERJA, DAN KELEMBAGAAN KOTA BANDUNG - Dadan Sidqul Anwar (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2009)
Bandung City as the Jakarta’s buffer and the Capital City of West Java has attracted immigrants which result in the increasing number of its population. This phenomenon has led to growing unemployment rate. Fiscal decentralization is believed to be able to solve the problem. In this study, the writer wants to investigate the impacts of budget allocation on some sectors to Bandung Cityoutput, income, employment, and the institution. Input-output and descriptive analyses are deployed in analyzing the data. The result proves that hotel and communication sectors have a significant role in Bandung economy. Their multiplier effect and linkage are high. The impact of fiscal decentralization on those sectors on output and income is high. However, Bandung City institution tends to be inefficient in budget allocation as well as at operational level.